ANALISIS PENGARUH FAKTOR FUNDAMENTAL PERUSAHAAN DAN RISIKO SISTEMATIS TERHADAP RETURN SAHAM - Arina Absari, Dyatri Utami; Sudarma, Made; Chandrarin, Grahita (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
This research aim to know influance of fundamental factors as financial ratio with proxy liquidity, asset size, debt equity ratio (DER), return on equity (ROE), earnings per share (EPS), price earnings ratio (PER) and systematic risk to the rate of return in Indonesian Stock Exchange. Manufacturing company as sample the taken amount to 54 emiten the listed in Indonesia Stock Exchange with period of research between of 2008 up to year of 2011. Analysis method the used is multiple linear regression. Analysis results indicate that from some element fundamental factor be likeÂ liquidity, asset size, debt equity ratio (DER), return on equity (ROE), earnings per share (EPS), price earnings ratio (PER) and systematic risk simultanly there are the influence significant to the profitability represented by rate of return. Partially show only earnings per share (EPS) and systematic risk with explained by variation the expressed in adjusted R2 equal to 7,8 % is while the rest equal to 92,2 % influenced by other variable which is not explained by this research model. Where as other variable not influence with models is liquidity, asset size, debt equity ratio (DER), return on equity (ROE) and price earnings ratio (PER). Research result pursuant to hypothesis test indicate that between some element fundamental factors is most dominant influence the rate of return at the manufacturing company of listed in Indonesia Stock Exchange is systematic risk. Â